2011
DOI: 10.1038/clpt.2010.317
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Smoking-Cessation Outcomes for a Novel Nicotine Immunotherapeutic

Abstract: NicVAX®, a nicotine vaccine (3’AmNic-rEPA), has been clinically evaluated to determine if higher antibody concentrations are associated with higher smoking abstinence rates and if doses and frequency of administration are associated with increased antibody response. This randomized, double-blinded, placebo-controlled multicenter clinical trial (N=301 smokers) tested 200 and 400 µg doses administered 4 or 5 times over 6 months compared to placebo. 3’AmNic-rEPA recipients with the highest serum anti-nicotine ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
225
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(229 citation statements)
references
References 15 publications
2
225
1
1
Order By: Relevance
“…These concentrations are higher than have generally been reported with nicotine or cocaine vaccines using similar linkers and carrier proteins, suggesting that opioid-based haptens are particularly immunogenic, perhaps due to their larger size (Kantak et al, 2000;Keyler et al, 2008;Roiko et al, 2008;Pravetoni et al, 2012a). In clinical trials of nicotine or cocaine vaccines, serum antibody concentrations have been considerably lower than those elicited in animals and this likely contributed to their limited efficacy in reducing smoking or cocaine use (Martell et al, 2009;Hatsukami et al, 2011;Esterlis et al, 2013). If opioid vaccines prove more immunogenic than nicotine or cocaine vaccines in humans this could substantially improve their chances of showing clinical efficacy against opioid abuse, but this has to be addressed in humans.…”
Section: Discussionmentioning
confidence: 61%
“…These concentrations are higher than have generally been reported with nicotine or cocaine vaccines using similar linkers and carrier proteins, suggesting that opioid-based haptens are particularly immunogenic, perhaps due to their larger size (Kantak et al, 2000;Keyler et al, 2008;Roiko et al, 2008;Pravetoni et al, 2012a). In clinical trials of nicotine or cocaine vaccines, serum antibody concentrations have been considerably lower than those elicited in animals and this likely contributed to their limited efficacy in reducing smoking or cocaine use (Martell et al, 2009;Hatsukami et al, 2011;Esterlis et al, 2013). If opioid vaccines prove more immunogenic than nicotine or cocaine vaccines in humans this could substantially improve their chances of showing clinical efficacy against opioid abuse, but this has to be addressed in humans.…”
Section: Discussionmentioning
confidence: 61%
“…Some vaccinees make a lot of antibodies, others relatively few (CDC, 2015). This is also the case with NV (Hatsukami et al, 2011). A fundamental difference, however, concerns the link between the protection of the individual and the group.…”
Section: From Testing Conditions To the Real Worldmentioning
confidence: 96%
“…A randomized, double-blinded, placebo-controlled multicenter clinical trial conducted in a sample of 301 smokers evaluated NicVAX at doses of 200-and 400-µg administered four or five times over a period of 6 months, as compared with placebo. The results showed that subjects with the highest serum anti-nicotine antibody response were significantly more likely to achieve 8 weeks of continuous abstinence from weeks 19 through 26 than those who received placebo inject ion (Hatsukami et al, 2011). Nabi Pharmaceuticals recently completed two phase III clinical trials of the NicVAX® for smoking cessation.…”
Section: Nicvaxmentioning
confidence: 99%